1992
DOI: 10.1016/0014-5793(92)81432-l
|View full text |Cite
|
Sign up to set email alerts
|

ATP‐sensitive K+‐channels in the human adult ventricular cardiomyocytes membrane

Abstract: Using tile patch-clamp method in 27 different reside-out patches it was shown for the first time that they defined tile basic parameters of tile functioning of tangle ATP-~ensitive K + channels in the human adult ventricular cardiomyocytes membrane. At [K+]o = 140 mM ~ingi~ channel conductance (over tile linear part of the 1-I-' relation) reaches 100 pS. The possibility of tile existence of the~e channels' conductance sublevels a~ well as the clunter character of their localization in sarcolemma is ~hown. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…This hypothesis is consistent with only a small fraction, ϳ1%, of the maximal NP O for K ATP channel population participating in the regulation of insulin secretion from pancreatic ␤-cells (12) or shortening of action potentials of metabolically inhibited ventricular cardiomyocytes (13,14). The hypothesis is consistent with the marginal effect of a decreased submembrane concentration of ATP on K ATP channel activity in situ, e.g.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…This hypothesis is consistent with only a small fraction, ϳ1%, of the maximal NP O for K ATP channel population participating in the regulation of insulin secretion from pancreatic ␤-cells (12) or shortening of action potentials of metabolically inhibited ventricular cardiomyocytes (13,14). The hypothesis is consistent with the marginal effect of a decreased submembrane concentration of ATP on K ATP channel activity in situ, e.g.…”
supporting
confidence: 74%
“…Cardiomyocyte Preparation-Human cardiac myocytes were isolated from specimens of myocardium taken from six patients, aged 6 -44 years, during cardiac surgery involving atrial appendage, as described previously for isolation of human ventricular cells (26), except a 2-fold lower concentration of Pronase E was used. Neonatal rat cardiomyocytes were isolated and cultured as described previously (27).…”
Section: Methodsmentioning
confidence: 99%
“…In the study of Kakei et al (1985) on cardiac cells, various levels of subconductance states were reported at normal pHi, but their relative rarity precluded detailed analysis. Similar subconductance events were also observed in a recent report on IK,ATP from human ventricular myocytes at pHi 7.2 (Babenko et al, 1992), but again no detailed analysis was done. In the IK,ATP channel of rat skeletal muscle fibers, multiple subconductance levels appeared after adding and withdrawing the channel blocker adenine to the cytoplasmic side of the membrane (Weik, L6nnendonker & Neumcke, 1989).…”
Section: S U B C O N D U C T a N C E S T A T E S Of Ikatp C H A N N supporting
confidence: 80%
“…3 Rat ventricular cells were prepared as described previously. 29 Clearly striated, single cardiomyocytes with a length-to-width ratioϾ4, shown to have a zerocurrent potential of Ϫ69Ϯ2 mV (measured in 4 cells using the whole-cell configuration under quasi-physiological ionic conditions) were selected for patch-clamp experiments.…”
Section: Isolation Of Cardiomyocytesmentioning
confidence: 99%
“…These channels are abundant in mammalian cardiomyocytes, including adult human ventricular 3 and atrial 4 cells. Cardiac K ATP channels exhibit a rich regulatory phenomenology 5,6 whose underlying structure-function relationships have been difficult to investigate in the absence of a well-defined recombinant channel.…”
mentioning
confidence: 99%